Strategi penambahbaikan pengurusan bencana banjir besar di Kelantan - Ibrahim, Farisah (2016)
Flood was a natural disaster that is no stranger to the world community in general. Floods are the most devastating natural disasters that occurred in Malaysia. Since 1965 year flood has affected many areas in Malaysia, including floods in 2014. Malaysia’s National Security Council (NSC) said that the floods in Kelantan 2014 were the worst recorded in the history of the state. Kuala Krai one of the hardest hit areas with entire homes and villages being completely submerged in floodwater. The community in the Kelantan River Basin is still confronted by the problem of ineffectiveness of flood management system despite the government’s efforts to come up with various approaches on flood management systems to assist flood victims. Therefore, the management problem and strategy improvement during and after the flood tragedy is studied and identified respectively. The research scope is Kuala Krai, Kelantan. In this study, qualitative method is carried out where the respondents are five officers: two from State Level and three are from District Level. It is found that, eight problems are identified during and after flood management in 2014 tragedy. Meanwhile, three strategies of improvement during and one strategies after flood management are proposed. Further to that this study will be a good reference to other committee that involved in flood management system.